2020
DOI: 10.1038/s41598-020-73930-3
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of NOS3 rs2070744 genotypes on hepatocellular carcinoma patients treated with lenvatinib

Abstract: We investigated whether or not nitric oxide synthase 3 (NOS3) rs2070744 genotypes can affect the response for lenvatinib treatment in patients with hepatocellular carcinoma (HCC). We evaluated the relation of the NOS3 rs2070744 genotypes to the tumor response, progression-free survival (PFS), and overall survival (OS) as the response for lenvatinib. We also examined the association between fibroblast growth factor receptor (FGFR) gene polymorphisms, a potential feature of lenvatinib, and the response. There we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We also expected a correlation between the change in NO levels and HBP. Previous studies have shown that patients who experienced hypertension after administration of lenvatinib had signi cantly better outcomes than did those who did not develop these AEs [15]. A subsequent reduction in NO production lead to HBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also expected a correlation between the change in NO levels and HBP. Previous studies have shown that patients who experienced hypertension after administration of lenvatinib had signi cantly better outcomes than did those who did not develop these AEs [15]. A subsequent reduction in NO production lead to HBP.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, 68 patients were excluded due to the following exclusion criteria: (i) lenvatinib discontinued within 14 days, (ii) malignancies other than HCC, (iii) no genomic DNA extracted from blood, and ( ) end-stage liver failure. Therefore, the previous study analyzed 100 patients [15]. Of those patients, 30 did not receive blood serum to identify the biomarkers of the response of HCC to lenvatinib.…”
Section: Patientsmentioning
confidence: 99%
“…We also expected a correlation between the change in NO levels and HBP. Previous studies have shown that patients who experienced hypertension after lenvatinib administration had significantly better outcomes than those who did not develop AEs [ 15 ]. A subsequent reduction in NO production lead to HBP.…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed using previously collected data under another study that was conducted across three medical institutions in Japan from 2017 to 2020 [ 15 ]. The preliminary study enrolled 168 patients aged > 20 years who received lenvatinib for advanced or unresectable HCC (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation